Comparative Analysis of Service Quality at the Public Service Mall (MPPs) of Serang City and Cilegon City - Salsabila, Riezka; Handayani, Riny; Rahayu, Sierfi (Indonesian Journal of Social Science Research, 2026)
This study focuses on a comparative analysis of service quality at the Public Service Malls (MPP) in Serang City and Cilegon City. Research problems include differences in the number of operating service agencies, differences in the value of the Public Satisfaction Index, and disparities in the number of public consultations and complaints at both MPPs. The theory used is SERVQUAL according to Parasuraman in Tjiptono (2016:153) with five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The research method used is quantitative with inductive techniques, then the non-probability sampling technique uses the accidental sampling method through questionnaires to 98 respondents at the MPP in Serang City and 100 respondents at the MPP in Cilegon City. The validity of the data was tested by Validity Test, Reliability Test, Normality Test, Homogeneity Test, and Hypothesis Test using Independent Sample T-Test. The results of the hypothesis test show that the alternative hypothesis (H₁) is accepted, with a significance value of Sig. (2-tailed) = 0.001 < α = 0.10. Thus, the results of this study indicate a significant difference between the quality of public services of the two MPPs. The quality of public services in the Serang City MPP reached 76%, which is in the Good category. Meanwhile, the Cilegon City MPP achieved 83% which is in the Very Good category. Suggestions were given for the Serang City MPP to improve the cleanliness of its facilities and service flow, and for the Cilegon City MPP to improve the punctuality of service start times.